Role of neck dissection in the treatment of melanoma of the head and neck - Bodem, Jens; Gülicher, Dirk Lothar; Engel, Michael; Hoffmann, Jürgen; Freudlsperger, Christian (The journal of craniofacial surgery, 2013)
Despite numerous studies, specific guidelines for cervical lymph node surgery in cutaneous malignant melanoma of the head and neck are still missing. - In a retrospective study, the modalities of neck dissection (ND), the histologic results, and the outcome in 59 patients with cutaneous malignant melanoma of the head and neck were evaluated to verify the benefit of this therapy. - Patients with proven lymph node metastasis often benefit from complete ND because about 50% of the patients showed more metastases in their ND specimen than before surgery. In addition, suspicious but not surely malignant lymph nodes often proved to be benign. - This study reveals that patients with proven lymph node metastasis often benefit from complete ND because the number of infiltrated nodes is often higher than suspected; nevertheless, when planning the surgical therapy, the overall prognosis has to be kept in mind.
Gesehen am 27.11.2020